Features of medical care in patientswith elbow joint gunshot wounds - Loskutov, Aleksandr; Domanskyi, Andriy; Zherdev, Ivan; Lushnya, Svyatoslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
Gunshot wounds of the elbow joint are the third most common after knee and shoulder injuries. Features of the anatomical and functional structure of the elbow joint, the close location of the vascular and nervous formations, favorable conditions for the development of infection determine the severity of gunshot wounds and cause the complexity of its treatment. Objective. To evaluate the frequency and nature of the elbow joint gunshot wounds in the structure of the general combat injuries, as well as to determine the volume of medical care and direction of treatment of such injuries in the conditions of the regional hospital as a stage of care. Methods. A retrospective study included 1 809 patients (96.0 % of men, mean age (33.7 ± 0.2) years). Firearms limb injuries were detected in 1 013 (56.0 %) of all victims, of which the elbow joint — 25 (2.47 %). Mines and explosives injuries were in 22 (88 %) of the patients, bullet — in 3 (12 %). Results. Tactics of treatment of elbow joint gunshot wounds depended on the severity of the condition of the victims and the nature of concomitant traumatic injuries. In the structure of combat injury of the elbow joint the majority was combined (52 %) and multiple (40 %) injuries and was accompanied by gunshot fractures in 60 %. In patients who were in severe state, applied the tactics of Damage control in two stages. At the first stage the fractures were fixed with plaster splints or external fixation devices (EF), the wounds were not subjected to full surgical debridment (SD), but only washed with antiseptics and the visible foreign bodies were removed. In patients with soft tissue injuries wounds the primary SD was performed according to general principles, injured nerves were not restored. In the second stage, after patient is stabilized, the repeated SD of the wound was performed. After their uncomplicated healing the EF was removed and the method of fixation was changed to internal osteosyntesis. Conclusions. It is recommended to perform stabilization of intra-articular gunshot fractures of the elbow joint with EF and after uncomplicated wound healing go to the internal osteosynthesis. Key words. Elbow joint, gunshot wounds, treatment.